Cultural and Historical Lacunae in Translation The Context of “The Crying Steppe” - Kalyshbek, A. (MAQSUT NARIKBAYEV UNIVERSITY School of Liberal Arts. Astana, 2025)
This study investigates the translation of cultural lacunae in The Crying Steppe (Kunarova, 2020) film’s English subtitles to enhance audiovisual translation (AVT) for preserving Kazakh cultural identity. Addressing research questions aimed at identifying lacunae types and evaluating translation strategies’ impact, the research employs a product based qualitative study, analyzing 51 cultural lacunae in the film’s subtitles. The scope focuses on Kazakh-specific terms lacking direct English equivalents. Through translation analysis, five lacunae categories were identified: idioms, cultural expressions, cultural objects, customs, and historical lacunae. Results revealed dominant translation strategies, including generalization, functional analogue, omission, explication, calque, and transliteration. Generalization and omission often simplified meanings for accessibility and comprehension of the target audience, but diluted cultural nuances and historical weight, while explication and transliteration preserved some authenticity. The study concludes that these translation choices only partially conveyed the film’s Kazakh heritage and Soviet-era context, highlighting challenges in balancing comprehension with fidelity. Recommendations include using annotations, glosses, and culturally informed teams to retain cultural specificity in AVT translation. These findings have practical implications for AVT practitioners, translators, and filmmakers, offering strategies to improve translations of Kazakh films. By addressing lacunae translation challenges, the research contributes to authentic cultural representation, ensuring global audiences' appreciation of The Crying Steppe’s rich historical and cultural depiction
Keywords: lacunae, Kazakh lacunae, translation strategies, audiovisual translation, cultural translation, The Crying Steppe